Antifungal activity of Syzygium samarangense leaf extracts against Candida. (1st July 2021) - Raj, S.; Vinod, V.; Jayakumar, J.; Suresh, P.; Kumar, A.; Biswas, R.
Abstract: Candida species are opportunistic human fungal pathogens that cause acute and chronic infections against which only few antifungal agents are available. Here we have elucidated the antifungal effect of Syzygium samarangense leaf extracts (SSLE). Antifungal activity of SSLE was studied against Candida albicans, C. krusei, C. parapsilosis, C. glabrata, C. auris and C. tropicalis . Following experiments were performed: minimum fungicidal concentration (MFC) determination, agar well disc diffusion assays, fungal morphology analysis using scanning electron microscope (SEM), ex vivo fungal survival assays on porcine tongue and skin and in vivo fungal survival assays using Drosophila melanogaster fly model. Results demonstrated MFC of SSLE ranges between 100 and 125 mg ml −1 . SEM images showed cell wall degradation of C. albicans when treated with SSLE. Around 75% decrease in C. albicans viability was observed when infected porcine tongue and skin were treated using SSLE. The C. albicans infected D. melanogaster when fed with SSLE showed significant decrease (around 80%) of fungal count than the infected control. Furthermore, agar plate disc diffusion assays demonstrated that the antifungal activity of SSLE could be due to chalcone, which is one of the active constituents in SSLE. Our study demonstrated that SSLE could be used for the topical treatment of Candida infections.